Digestive Anxieties: Russian Projects of Bionational Citizenship - Caldwell, Melissa L. (Food & History, 2020)
Abstract During the communist period, Soviet officials emphasized the power of food in their projects to encourage appropriate political sensibilities and attain cultural progress. From new industrial food systems to public catering, and from culinary multiculturalism to modernist cuisine, Soviet consumers were promised that communist food practices would bring about higher standards of living, greater opportunities for pleasure and leisure, and healthier citizens and communities. Yet the gaze and reach of the state extended beyond the tables and shelves where foods were prepared, presented, and consumed, and into the most intimate spaces of citizens’ bodies. Nutritional recommendations, childrearing manuals, and community-oriented feeding regimes represented the state’s efforts to transform socialist values into visceral, corporeal, and even physiological phenomena. Today, efforts to fortify the Russian state through forms of bionational citizenship continue as state officials and consumers alike pursue new civic nutrition regimes. This article examines post-Soviet Russian efforts to create a strong and robust nation through the fortification of its most intimate boundaries - that of the stomach and the guts. Abstract Pendant la période communiste, les responsables soviétiques ont mis en avant le pouvoir de l’alimentation dans leurs projets afin d’encourager les sensibilités politiques appropriées et atteindre le progrès culturel. Des nouveaux systèmes alimentaires industriels à la restauration publique et du multiculturalisme culinaire à la cuisine moderniste, les consommateurs soviétiques se sont vus promettre que les pratiques alimentaires communistes amèneraient des niveaux de vie plus élevés, de plus grandes possibilités de plaisirs et de loisirs et des citoyens et communautés en meilleure santé. Pourtant, le regard et la portée de l’État dépassèrent les tables et étagères où les aliments étaient préparés, présentés et consommés, et allèrent jusque dans les espaces les plus intimes du corps des citoyens. Les recommandations nutritionnelles, les manuels d’éducation infantile et les régimes alimentaires communautaires représentèrent les efforts étatiques pour transformer les valeurs socialistes en phénomènes viscéraux, corporels et même physiologiques. Aujourd’hui, les efforts afin de fortifier l’État russe grâce à des formes de citoyenneté bionationale continuent, alors que les responsables de l’État et les consommateurs poursuivent de nouveaux régimes de nutrition civique. Cet article examine les efforts que la Russie post-soviétique a mis en oeuvre pour créer une nation forte et robuste en fortifiant ses frontières les plus intimes : celles de l’estomac et des tripes.